THE TEACHINGS TO REACH LIFE SAFETY AND CHARACTER VALUES IN SERAT GEMBRING BARING - Baktya Tri Setiono; Endang Nurhayati (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
This research aims to (1) inventory and describe the manuscript of Serat Gembring Baring, (2) display and describe the teachings to reach life safety in the manuscript, (3) explain the character values in the manuscript.  The data are all text or lyrics song in the manuscript. The type of this research was descriptive research with a content analysis method. The process of collecting the data is done by reading technique, taking note and also selecting or reducing the data. The data were analysed descriptively. The validity of the data was gained through semantic validity. Intrarater and interrater reliabity was used to gain the reliability of the data. From the results of the analysis, there are 11 text of Serat Gembring Baring and the manuscript used in this research is still well. There were 6 things that must be done to achieve safety, 1) must have knowledge; 2) must learn about theology (Islam) and science of Java; 3) do the goodness; 4) stay away from the bad things; 5) always pray; and 6) have faith. There are 10 character values in Serat Gembring Baring still related to present life, including religiousity, honesty, discipline, preserance, democracy, curiousity, respect, friendliness, sociability, and responsibility.